‘Oh God, I have to eat something, but where can I get something quickly?': a qualitative interview study on barriers to healthy eating among university students in Germany - Hilger-Kolb, Jennifer; Diehl, Katharina (Nutrients, 2019)
Healthy eating can prevent individuals across all age groups from developing overweight/obesity and non-communicable diseases such as type 2 diabetes and cardiovascular disease. However, unhealthy eating habits (e.g., a high level of fast food consumption) have been found to be widespread among university students. Thus, it seems necessary to develop prevention strategies to improve students’ eating habits. However, to ensure that such strategies are successful, it is important that they fit the needs of the target population. By conducting qualitative interviews with students (n = 20), we aimed to get a deeper understanding of barriers to healthy eating. Students were asked about barriers to healthy eating and to suggest possible ideas that could improve their eating behavior in the future. Our findings revealed that students are especially affected by time-related barriers (e.g., a lack of time due to university commitment) and environmental barriers (e.g., a lack of cheap, tasty, and healthy meal options at the university canteen). Time-related barriers were also related to motivational barriers (e.g., being too lazy to cook after a busy day at university). In addition, knowledge/information-related barriers, social-support-related barriers, and transition-related barriers emerged from our interviews. The variety of barriers addressed and the different views on some of these, indicate that various strategies seem to be needed to improve the eating behavior among university students and to prevent them from gaining weight and developing non-communicable diseases in the future.